(untitled) (Medico Legal Update, 2020)
The research included the study of microbiological content in the reproductive system and urinary tract infections for abortions cases in the city of Fallujah. For this purpose, 121 swabs were taken, including 50 swabs of the genital system (27 Vaginal and 23 Endo cervical swabs) and 71 swabs of urine. The result refer to that only 27 samples gave negative bacterial growth, while the other 94 samples showed growth of more than one species of bacteria on different media. The bacterial population isolated from the urine was highest (81.7%), followed by vagina (74.1%) and the endo cervical (69.6%%).The results showed that the ratios of the isolated bacterial samples were Escherichia coli (54.4%), Streptococcus agalactiae (17%), Staphylococcus aureus (12%), Klebsiella (8.5%), Pseudomonas aeruginosa (5.3%), Proteus (1%) and Candida albicans (1%). The E. coliwas the most common type bacterial isolates.Antibiotic sensitivity tests against 24 antibiotics were reveal that bacteria Escherichia colihave multiple resist against different antibiotics, most isolates were highly resistant to Aztroenam followed by cefotaxime and ciproflaxime respectively, while their resistance to other antibiotics varied.The results also showed that Proteus which isolated from urine samples and Candida albicans which isolated from vaginal specimens were the lowest percentage, where only one isolate was obtain for each and the Candida abicans were resistant to all of different antibiotics used in this study.